PENGUASAAN TANAH MELALUI PERJANJIAN PINJAM NAMA (NOMINEE) OLEH WARGA NEGARA ASING - Devy Larasati, Luh; Sudantra, I Ketut (Kertha Semaya : Journal Ilmu Hukum; Vol. 01, No. 10, Oktober 2013, 2013)
The acquisition of land by foreign nationals using the name and loan agreements (Nominee) there is the letter of the agreement made by the parties, namely between foreign nationals and citizens of Indonesia as an authorizer (Nominee), which was created through a package of agreements that the principal agreement and additional agreements are ultimately intended to provide any authority that may arise in the legal relationship between a person and his land to foreign citizens as an authorized representative to act like an actual owner of a parcel of land which legally can not be owned. The formulation of the issues raised is how the legal consequences of land ownership through loan covenant name (Nominee). This research is a normative law, with the approach of legislation and legal analysis, which is based on sources of primary legal materials and secondary legal materials, as well as analysis by way of description and argument. Based on the discussion of this study, the results obtained are due to the legal name of the loan agreement (Nominee) impact on the status of land rights, the validity of the agreement, and land ownership disputes.
Keywords: Land Tenure, Lending Agreements Name (Nominee), Foreigners, A Result of The Law